2015
DOI: 10.3390/s150819102
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Concentrations of Toxic VOCs in the Ambient Air of Gumi, an Electronics-Industrial City in Korea

Abstract: This study was carried out to characterize the occurrence and concentrations of a variety of volatile organic compounds (VOCs) including aliphatic, aromatic, halogenated, nitrogenous, and carbonyl compounds, in the ambient air of Gumi City, where a large number of electronics industries are found. Two field monitoring campaigns were conducted for a one year period in 2003/2004 and 2010/2011 at several sampling sites in the city, representing industrial, residential and commercial areas. More than 80 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…VOCs The VOC measurement method was based on the USEPA TO-17 protocol, which has been used in several field studies (Baek et al 2015(Baek et al , 2020aKim, et al 2020;Seo et al 2014). VOCs were collected twice per day (09:00−12:00 and 14:00−17:00) by drawing air through a stainless-steel tube (0.6 mm x 9 cm, Perkin Elmer, UK) packed with double sorbents: 120 mg and 280 mg of Carbograph-2TD and Carbograph-1TD (40/60 mesh, Markes, UK) in the front and back positions, respectively.…”
Section: Measurement Of Vapor Phase Hapsmentioning
confidence: 99%
“…VOCs The VOC measurement method was based on the USEPA TO-17 protocol, which has been used in several field studies (Baek et al 2015(Baek et al , 2020aKim, et al 2020;Seo et al 2014). VOCs were collected twice per day (09:00−12:00 and 14:00−17:00) by drawing air through a stainless-steel tube (0.6 mm x 9 cm, Perkin Elmer, UK) packed with double sorbents: 120 mg and 280 mg of Carbograph-2TD and Carbograph-1TD (40/60 mesh, Markes, UK) in the front and back positions, respectively.…”
Section: Measurement Of Vapor Phase Hapsmentioning
confidence: 99%
“…Since the occurrence of photochemical smog disaster in Los Angeles (Brown et al, 2007), VOCs have gradually attracted more and more attentions. Under the action of ultraviolet light, VOCs originated from motor vehicle exhaust gases, industrial discharges and fuel combustion products eventually become toxic gases that may cause disease or death (Baek et al, 2015). Na et al (2004) and Alvim et al (2018) found that controlling VOCs emissions can effectively reduce photochemical smog.…”
Section: Introductionmentioning
confidence: 99%
“…VOCs play a vital role in the formation of ozone (Berezina et al, 2017;Olumayede et al, 2014) and photochemical oxidants (Derstroff et al, 2017). Recently many researchers have focused on the VOCs BTEX compounds (benzene, toluene, ethyl benzene and xylene) due to their toxicity and well correlated with each other (Bretón et al, 2017;Baek et al, 2015;Kerchich et al, 2012;Miller et al, 2010Miller et al, , 2009Hoque et al, 2008).…”
Section: Introductionmentioning
confidence: 99%